Grafito con temática naval del Geométrico griego. A propósito de las galeras eubeas con pie de mástil sobre caballete - Guerrero Ayuso, Víctor M. (Gerión. Revista de Historia Antigua, 2009)
This article analyses an engraving with a naval theme that is highly useful in ascertaining and correctly identifying pre-classical Euboean galleys, a kind of vessel with different elements of naval architecture from its contemporaries in Attica and the Peloponnesian Islands. One extraordinarily interesting aspect is that the author of this engraving was a sailor, which endows this iconographic document with a highly significant testimonial value.
Keywords: Galley; Euboean; Geometric style; Mast; Trestle